Hematopoietic stem cell boost for persistent neutropenia after CAR T-cell therapy: a GLA/DRST study - Gagelmann, Nico; Wulf, Gerald Georg; Duell, Johannes; Glaß, Bertram; Heteren, Pearl van; Tresckow, Bastian von; Fischer, Monika; Penack, Olaf; Ayuk, Francis; Einsele, Herrmann; Holtick, Udo; Thomson, Julia; et al. (Blood advances, 2023)
Hematotoxicity after chimeric antigen receptor (CAR) T-cell therapy is associated with infection and death but management remains unclear. We report results of 31 patients receiving hematopoietic stem cell boost (HSCB; 30 autologous, 1 allogeneic) for either sustained severe neutropenia of grade 4 (<0.5 × 109/L), sustained moderate neutropenia (≤1.5 × 109/L) and high risk of infection, or neutrophil count ≤2.0 × 109/L and active infection. ...
Online-Vorabveröffentlichung: 13. Juni 2022
Gesehen am 16.11.2023